2021
DOI: 10.3389/fmolb.2021.763958
|View full text |Cite|
|
Sign up to set email alerts
|

Comprehensive Analysis of the Potential Immune-Related Biomarker Transporter Associated With Antigen Processing 1 That Inhibits Metastasis and Invasion of Ovarian Cancer Cells

Abstract: Transporter associated with antigen processing 1 (TAP1) is a protein related immune regulation and plays a role in several malignant tumors. However, the effect of TAP1 on immune infiltration, immunotherapy, and metastasis in different cancers has not been reported till date. The cancer genome atlas database, the tumor immune estimation resource database, and the estimation of stromal and immune cells in malignant tumors using expression (ESTIMATE) algorithm were used to determine the correlation between TAP1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Anika Tabassum et al found that prognostic analysis on the OV showed a positive correlation for TAP1 expression, while it is negative on BRCA, LIHC, and LUAD [ 11 ]. In patients with ovarian cancer, TAP1 protein abundance was negatively correlated with survival time and significantly correlated with immune infiltration and poor prognosis [ 12 ].Therefore, there is no consistent relationship between TAP1 expression and patient prognosis in different cancer types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anika Tabassum et al found that prognostic analysis on the OV showed a positive correlation for TAP1 expression, while it is negative on BRCA, LIHC, and LUAD [ 11 ]. In patients with ovarian cancer, TAP1 protein abundance was negatively correlated with survival time and significantly correlated with immune infiltration and poor prognosis [ 12 ].Therefore, there is no consistent relationship between TAP1 expression and patient prognosis in different cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…TAP1 is involved in antigen transport from the cytoplasm to the endoplasmic reticulum, binds to major histocompatibility complex (MHC) class I molecules, forms the molecular scaffold for the final stage of MHC class I folding, and then presents MHC I to immune cells, thereby serving as a target for tumor cells [ 10 ]. Recent studies have shown that TAP1 is closely associated with various tumors and has the potential to become a novel tumor-targeting drug [ 11 , 12 ]. Although high TAP1 expression might, in theory, make tumor cells more susceptible to cytotoxic T cell killing [ 13 ], it might reduce their susceptibility to natural killer (NK) cell–mediated lysis [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In ovarian cancer, overexpression of TAP1 in OC patients leads to a poor prognosis. The high expression of TAP1 promotes tumor migration and metastasis in vivo and in vitro ( 58 ). Our study confirmed the increased mRNA levels of TAP1 in ccRCC, both in the TCGA cohort and in the FUSCC cohort, as well as the increased protein expression in the proteomic study.…”
Section: Discussionmentioning
confidence: 99%
“…One strategy is to target and mute the immune regulators, so that functional immune signal processing is blocked, facilitating cancer cell survival. Here, 47 common ICP genes were selected and analyzed in the context of TAP1 expression, using previously described methods [29]. Spearman's correlation analysis was conducted to evaluate the correlations between TAP1 expression and levels of individual ICPs across TCGA pan-cancer types (Fig.…”
Section: Correlation Between Tap1 Expression and The Tmementioning
confidence: 99%